Bright metal coatings from sustainable electrolytes: the effect of molecular additives on electrodeposition of nickel from a deep eutectic solvent. Issue 4 (13th January 2017) - Abbott, Andrew P.; Ballantyne, Andrew; Harris, Robert C.; Juma, Jamil A.; Ryder, Karl S.
Abstract : Small molecule organic additives produce smooth, bright, adherent and hard nickel coatings during electrodeposition in a deep eutectic solvent. We present a detailed study. Abstract : Organic and inorganic additives are often added to nickel electroplating solutions to improve surface finish, reduce roughness and promote uniform surface morphology of the coatings. Such additives are usually small molecules and often referred to as brighteners or levellers. However, there have been limited investigations into the effect of such additives on electrodeposition from ionic liquids (ILs) and deep eutectic solvents (DESs). Here we study the effect of four additives on electrolytic nickel plating from an ethyleneglycol based DES; these are nicotinic acid (NA), methylnicotinate (MN), 5, 5-dimethylhydantoin (DMH) and boric acid (BA). The additives show limited influence on the bulk Ni(ii ) speciation but have significant influence on the electrochemical behaviour of Ni deposition. Small concentrations ( ca. 15 mM) of NA and MN show inhibition of Ni(ii ) reduction whereas high concentrations of DMH and BA are required for a modest difference in behaviour from the additive free system. NA and MN also show that they significantly alter the nucleation and growth mechanism when compared to the additive free system and those with DMH and BA. Each of the additive systems had the effect of producing brighter and flatter bulk electrodeposits with increased coating hardness but XRD shows that NA and MN direct crystal growth to the [111] orientation whereas DMH and BA direct crystal growth to the [220] orientation.